Navigating health information chaos: Perspectives from Persian-speaking immigrants in Finland - Arzideh, Sara; Ahmadinia, Hamed (Finnish Journal of eHealth and eWelfare, 2023)
The purpose of this study is to explore health information environment and behaviours of Persian-speaking immigrants in Finland during the COVID-19 pandemic, utilising information chaos framework. Between January to March 2022, semi-structured interviews were conducted with a sample of 18 participants, using an adapted framework of information chaos and previous research as a guide for the interview questions. The study found that participants relied on interpersonal connections, news outlets, and social media to stay informed on current news and health-related information, with messaging apps being particularly popular due to their convenience and ability to connect with friends and family in their home countries. While most participants were satisfied with the amount of information they received, some encountered inaccurate pandemic information. The study also identified significant obstacles related to information scatter and conflict. Participants employed various methods, including verifying with official sources and interpersonal networks, to assess the reliability of their information. Credible health information led to changes in behaviour and lifestyle. The study's findings offer practical implications for health authorities and policymakers to address the health information needs of Persian-speaking immigrants during public health crises. The use of an information-chaos framework could be beneficial in identifying challenges related to channelling accurate and reliable health information among minorities through different information sources. Such initiatives can bridge the gap between the health information needs of immigrants and the available health information, ultimately reducing health disparities and improving health outcomes. This study represents one of the pioneering works exploring the information environment during a pandemic and the strategies adopted by the Persian-speaking minority to address the dissemination of false information during a health crisis. These findings shed light on the complex interplay of individual and health information environments that influence adhering to safety protocols and adopting healthy behaviours in this population.